2015
DOI: 10.1097/qad.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Improving care for patients on antiretroviral therapy through a gap analysis framework

Abstract: The ART Framework is an innovative and practical tool for HIV program managers to improve HIV care and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We grouped approaches into 4 main categories with support from experts in the Quality of HIV Care Technical Working Group (Fig. 1): health systems approaches using QI methods (n = 20), 21,22,2426,29–43 standard-based methods that use QI tools to improve performance gaps (n = 2), 17,23 campaigns that use QI methods (n = 1), 28 and QI learning networks including collaboratives (n = 6). 15,16,1820,27 Initiatives were performed in 13 LMICs, including South Africa, 15,19,20,28 Vietnam, 16,35 Zambia, 17,23 Nigeria, 18,27 Uganda, 21,22,31,36,40 Mozambique, 21,22 Namibia, 21,22,29,34,42,43 Haiti, 21,22,24,32,36,41 Thailand, 25,26 Nicaragua, 33 Kenya, 38 Tanzania, 37 and Guyana, 34,39 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We grouped approaches into 4 main categories with support from experts in the Quality of HIV Care Technical Working Group (Fig. 1): health systems approaches using QI methods (n = 20), 21,22,2426,29–43 standard-based methods that use QI tools to improve performance gaps (n = 2), 17,23 campaigns that use QI methods (n = 1), 28 and QI learning networks including collaboratives (n = 6). 15,16,1820,27 Initiatives were performed in 13 LMICs, including South Africa, 15,19,20,28 Vietnam, 16,35 Zambia, 17,23 Nigeria, 18,27 Uganda, 21,22,31,36,40 Mozambique, 21,22 Namibia, 21,22,29,34,42,43 Haiti, 21,22,24,32,36,41 Thailand, 25,26 Nicaragua, 33 Kenya, 38 Tanzania, 37 and Guyana, 34,39 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] Another traced patients lost to follow-up by conducting home visits, and for patients unable to travel to the clinic, they introduced outreach visits. [ 34 ] Roland et al, described the evaluation of multiple pilots for care of elderly patients, which offloaded work from patients through intensive team communication about patients most at risk for admission to the hospital and rapid follow-up by phone or home visits as needed for patients. [ 35 ] In many of these pilot sites, community and social services and home-care services were deployed.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the CCM on a variety of chronic diseases has been reported, including asthma, diabetes, and depression (Improving Chronic Illness Care [ICIC], 2018). Only seven studies, however, have been retrieved on the application of the CCM to HIV/AIDS (Goetz et al, 2008; Drabo et al, 2010; Tu et al, 2013; Clarke et al, 2015; Mahomed and Asmall, 2015; Massoud et al, 2015; Berenguer et al, 2018). These studies reported improved access and adherence to antiretroviral therapy, implementation of pertinent interventions, and increased involvement of PLWHA with their own care, resulting in clinical, immunological, and virological gains.…”
Section: Introductionmentioning
confidence: 99%